FINANCIAL FEASIBILITY OF IMPLEMENTING SMART SAFETY TECHNOLOGIES IN ELECTRICAL ENGINEERING PROJECTS: A REVIEW OF CURRENT STATUS AND FUTURE PROSPECTS - Muhammad Waqas Aslam; Saima Aslam; Naila Aslam; Tehmina Aslam; Jawaria Aslam (Spectrum of Engineering Sciences, 2025)
This study investigated the financial viability of implementing smart safety technologies in electrical engineering projects by analyzing cost-benefit metrics, return on investment patterns, and implementation challenges across various project scales. The research utilized a mixed-methods approach combining quantitative financial analysis of 78 electrical engineering projects and qualitative assessments through 42 expert interviews to evaluate how safety-oriented smart technologies impact project economics. Results revealed that mid-to-large scale projects achieved ROI breakeven within 18-24 months post-implementation, while smaller projects experienced longer cost recovery periods averaging 32-38 months. The study identified five critical cost factors affecting implementation feasibility: initial capital requirements, integration complexity with existing systems, specialized workforce training needs, maintenance costs, and regulatory compliance expenses. This research contributes to understanding the economic dimensions of safety technology implementation in electrical engineering, offering practical guidelines for project stakeholders to maximize financial benefits while prioritizing safety standards. The findings provide a framework for electrical engineering firms to assess implementation costs against long-term financial and safety benefits.